NEURAL NETWORK MODELING OF RECOGNITION PROCESSES OF CATEGORIES OF SENSE AND ABSURDITY IN INTERNET DISCOURSE - Dovhan , Oleksii (Collection of scientific papers «ΛΌГOΣ», 2023)
Internet discourse is a special type of discourse characterized by polyinterpretation. Naturally, such an environment offers an unlimited number of opportunities for communication, occupying an increasingly large part of a modern person’s life. At the same time, the communication component is a core aspect of Internet culture, as it is a relevant indicator of user behavior. However, along with the increasing actualization of online discourse for communication, a number of problems arise related to the existence of the categories of sense and absurdity in it.